Lattice‐based unidirectional Proxy Re‐Encryption and Proxy Re‐Encryption+ schemes - Kunwar Singh; C. Pandu Rangan; Samir Sheshank; Richa Agrawal (IET Information Security)
Abstract The concept of Proxy Re‐Encryption (PRE) was introduced by Blaze, Bleumer and Strauss at Eurocrypt in 1998. In this concept, a semi‐trusted proxy user acquires a re‐encryption key from the delegator. Then the proxy can easily convert the encrypted message under Alice's public key into an encrypted message under Bob's public key, without knowing the content of the message. For a unidirectional PRE, a master secret security (MSS) has been proposed as another security requirement by Ateniese et al. MSS provides security to the secret key of the delegator from computation by association with a malicious delegatee and dishonest proxy. In this study, first we have shown that Aono et al.'s scheme is not secure under the MSS model. Second, we have designed a unidirectional PRE scheme, based on Aono et al.'s study, and proved its security under the MSS model. In Table 2, we have shown that our scheme is more efficient in terms of computational and communication costs. Third, we have constructed a lattice‐based unidirectional PRE+ scheme, similar to the scheme proposed by Wang et al. In this scheme the encryptor itself works as the delegator.